Minireview: Addressing the retro-Michael instability of maleimide bioconjugates. (December 2018) - Szijj, Peter A.; Bahou, Calise; Chudasama, Vijay
Graphical abstract: Abstract : Bioconjugation, the modification of biological macromolecules such as proteins, is an up and coming area in the field of chemical biology. Antibody-drug conjugates (ADCs), combining the antigen-selectivity of natural antibodies with the cytotoxic potency of small molecule drugs, are a powerful therapeutic technology. Four such constructs are currently on the market for cancer therapy. However, the conjugation methodology employed in these therapeutics is far from ideal. Herein we provide an overview on methods that attempt to increase the safety and efficacy of ADCs via "self-hydrolysing maleimides" or by improving the stability of maleimide-conjugates by other means. We find that some very promising reagents have been reported, however the mechanism by which each of these reagents acts is not clear, thus limiting rational design for some strategies.